ADAB INTERAKSI PESERTA DIDIK DENGAN PENDIDIK DALAM PERSPEKTIF AL-QURAN SURAT AL-KAHFI AYAT 60-82 - Diana Putri; Pendi Hasibuan; Zulfani Sesmiarni; Salmi Wati (KOLONI, 2022)
Talking about adab today, there are several phenomena in the world of education. as a reflection of the decline in etiquette as education actors, both in terms of educational leaders, teachers and especially students. This condition will have an impact on the expected quality of education. One example is the manners of students who have almost disappeared from everyone. This can be seen by the number of students or students who do not have good manners in speaking, behaving and dressing that are not in accordance with the concept of Islamic teachings, violate morals, school regulations, code of ethics at the student level, it all shows that the damage to morals, morals and etiquette has been very worrying. Based on these problems, the formulation of the problem of this research is as follows: 1). How is the manners of students towards educators in the perspective of Al-Quran Surah Al-Kahf verses 60-82? 2). How is the relevance of students' etiquette to the educator in accordance with Islamic education? This study uses a qualitative approach with the type of library research. This research was carried out by relying on library data, namely by examining the verses of the Koran Surah Al-Kahf verses 60-82. In this study, the data analysis method that the author uses is descriptive qualitative method. After an in-depth study, it is known that there are interactions between students and educators in Surah al-Kahf verses 60-82, namely being polite to educators, being patient before understanding a science, obeying educators, apologizing if you make mistakes, not being angry with educators, ready to accept the consequences of mistakes that have been made, be kind to educators, then educators should not punish students for their forgetfulness, and provide explanations about the knowledge learned.  Keywords: Adab, Students, Educator, Surah Al-Kahf